Marketing Strategy on Fish Cultivation Products As An Effort to Increase Community Income (Study at JL. Tamalabba Manggatiga Paccerakkang) - Aprilia, Nadila; Risma Niswaty; Novayanti Sopia Rukmana (Business Research and Administration Innovation, 2025)
In the business world, it is inseparable from marketing theory. Marketing in In the business world, it is inseparable from marketing theory. Marketing in business is very important to introduce the goods or services offered to the general public. To offer products or services can be done by using existing social media by branding the products we have. The problem that then arises is how the marketing strategy applied by the cultivators related to fish cultivation on Jl. Tamalabba Manggatiga Paccerakang in increasing family economic income. Then what are the determinants of the marketing of fish farming products at that location. To achieve this goal, researchers used data collection techniques through observation, interviews, and documentation. The data obtained from the results of the research were processed using descriptive qualitative. The results showed that the marketing strategy implemented was a combination of the marketing mix, namely producing 4 indicators, namely product, distribution, promotion, and price. What was then carried out was a direct promotion process where the system went directly to the field to introduce what fish farming was like, hatchery to the product ready for harvest at what age and size. Then regarding the determinants of food produced by fish farming in that location, it can be seen from internal factors (strengths and weaknesses) and then external factors (opportunities and threats).